Step 1
Let Mackenzie have x
and Taylor have y
Then, since Mackenzie has 46.13 less than Taylor,
[tex]x=y-46.13[/tex]Therefore, to show how much money Mackenzie has we will use the equation;
[tex]\begin{gathered} x=y-46.13 \\ \text{Remember Mackenzie had \$x } \\ \text{Taylor had \$y} \\ \text{Mackenzie's money is less than Taylor's money by \$46.13} \\ So\text{ we take away \$46.13 from Taylor's money to get that of Mackenzie} \end{gathered}[/tex]Answer;
[tex]\begin{gathered} \text{Mackenzie's money(x)=Taylor's money (y)-46.13} \\ x=y-46.13 \end{gathered}[/tex]